The use of anthropogenic areas helps explain male brown bear movement rates and distance travelled during the mating season - Falcinelli, D.; del Mar Delgado, M.; Kojola, Ilpo; Heikkinen, S.; Lamamy, C.; Penteriani, V. (Wiley-Blackwell, 2024)
During the reproductive period, mating strategies are a significant driver of adapta tions in animal behaviour. For instance, for polygamous species, greater movement rates during the mating season may be advantageous due to the increased probabil ity of encountering several potential mates. The brown bear Ursus arctos is a soli tary carnivore that lives at low densities, with a polygamous mating system and an extended mating season of nearly 3 months. Here, we hypothesized that male brown bears may show changes in movement patterns and space-use behaviour during their mating season. Using long-term (2002–2013) telemetry data from the Finnish Karelia male population (n = 24 individuals; n = 10 688 GPS locations), we first analysed daily movement metrics, that is, speed, net and total distance with respect to the period (mating vs. post-mating) and several environmental predictors. Then, we conducted a step-selection analysis for each of these periods. Throughout the year, male bears selected forested/shrub habitats and increased movement rates near main roads. During the mating season, reproductive needs seem to trigger roaming behaviour in adult males to maximize encounter rates with potential recep tive females. However, all movement metrics increased within areas of high human activity, suggesting a bear response to a higher risk perception while using those areas. During the post-mating period, overlapping with the bear hyperphagia and the hunting season, males selected anthropogenic areas farther from main roads and trails, suggesting a trade-off between foraging opportunities and risk avoidance.
Keywords: brown bear; Ursus arctos; mating; movement patterns; movement ecology; step-selectionanalysis; multi-use landscape; human-modiﬁed landscape